Soluble MHC class I chain-related protein A is a specific biomarker for the early detection of graft-versus-host disease - Kupis, Alexander; Buchtele, Nina; Wohlfarth, Philipp; Rabitsch, Werner; Kovacevic Miljevic, Katarina D.; Mussbacher, Marion; Jilma, Bernd; Schoergenhofer, Christian (Frontiers in Medicine, 2025)
IntroductionMHC class I chain-related protein A (MICA) acts as a marker of cellular stress and its expression is a destruction-signal for NKG2D-expressing cytotoxic cells. Soluble MICA (sMICA) concentrations after allogeneic hematopoietic stem cell transplantation (HSCT) were associated with worse outcomes and graft-versus-host disease (GVHD). We hypothesized that (i) sMICA could be a prognostic biomarker for the development of GVHD and (ii) may act as an acute phase reactant.MethodsIn this prospective study we included 48 patients undergoing HSCT and drew blood samples before conditioning (baseline), during engraftment and 100 days after HSCT. The follow-up period was 1 year for each patient. Soluble MICA and established acute phase reactants (C-reactive Protein, von Willebrand Factor) were measured by enzyme-linked immunoassay (ELISA).ResultsOf the 44 patients in the final analysis, 30 (68%) developed GVHD (16 acute GVHD, 8 chronic GVHD, 6 acute and chronic GVHD). Soluble MICA concentrations at baseline and during engraftment were significantly higher in patients who developed acute or chronic GVHD (p = 0.017). Receiver operating characteristic (ROC) curve analysis for the baseline values showed an area under the curve of 0.78 (p < 0.001; 95% confidence intervals 0.64–0.91) for diagnosis of acute or chronic GVHD. Soluble MICA concentrations above 93.5 pg/mL had a specificity of 93% for the diagnosis of GVHD, while the sensitivity was only 47%.DiscussionSoluble MICA did not correlate with other acute phase reactants and remained stable during engraftment. Soluble MICA may potentially serve as a biomarker with high specificity for the prediction of GVHD.